A Multilevel Meta-Analysis of Dynamic Risk Factors for Emerging Adults who Abuse their Parents - Close, Simone B. (Journal of family violence, 2024)
PurposeEven though five to 11% of child-to-parent abuse (CPA) perpetrators are emerging adults (age 18–23 years), relevant risk factors underlying CPA in this group are understudied.MethodA multilevel meta-analysis was performed on nine studies (450 effect sizes, N = 1,043), comprising eight static (e.g., age and gender of perpetrator) and dynamic (e.g., substance abuse, financial problems) risk factors.ResultsEmerging adults who fell victim of domestic violence, or had antisocial cognitions, authority problems, or empathy problems displayed CPA more often. Moderator analyses revealed that the relation between gender of perpetrator and CPA was moderated by gender of victim (p = .033) and CPA type (p = .021). Gender of victim (p < .001) also moderated the relationship between single-parent household and CPA. Finally, the relation between witness to DV and CPA was moderated by age (p = .007).ConclusionsThis was the first multilevel meta-analysis focusing exclusively on CPA displayed by emerging adults. The results can be used as a basis for further research into relevant risk factors for CPA in this group and hopefully contribute to the development of health care interventions to reduce chances of CPA occurring.